Enhanced Drug Delivery by Dissolution of Amorphous Drug Encapsulated in a Water Unstable Metal–Organic Framework (MOF) - Suresh, Kuthuru; Matzger, Adam J. (Angewandte Chemie (International ed.), 2019)
Encapsulating a drug molecule into a water‐reactive metal–organic framework (MOF) leads to amorphous drug confined within the nanoscale pores. Rapid release of drug occurs upon hydrolytic decomposition of MOF in dissolution media. Application to improve dissolution and solubility for the hydrophobic small drug molecules curcumin, sulindac, and triamterene is demonstrated. The drug@MOF composites exhibit significantly enhanced dissolution and achieves high supersaturation in simulated gastric and/or phosphate buffer saline media. This combination strategy where MOF inhibits crystallization of the amorphous phase and then releases drug upon MOF irreversible structural collapse represents a novel and generalizable approach for drug delivery of poorly soluble compounds while overcoming the traditional weakness of amorphous drug delivery: physical instability of the amorphous form. MOF carrier: A drug delivery strategy where a metal–organic framework inhibits crystallization of the amorphous drug phase and then releases the drug upon hydrolytic decomposition represents a novel approach for delivery of poorly soluble compounds while overcoming the traditional weakness of amorphous drug delivery: physical instability of the amorphous form.